Hysterectomy and Adenextomy via transvaginal natural orifice transluminal endoscopic surgery (vNOTES): A UK perspective with a case series of 33 patients. (November 2019) - Karkia, Rebecca; Giacchino, Tara; Taylor, Jody; Ghaffar, Ammara; Gupta, Abishek; Kovoor, Elias
Abstract: Objective: : To evaluate operative outcomes of hysterectomy +/- adnexectomy by Trans-vaginal Natural Orifice Endoscopic Surgery (vNOTES) in a case series of 33 patients. Study Design: : It was a prospective case series study carried out in Darent Valley and Benenden Hospital, to our knowledge, the first units in the United Kingdom to have undertaken VNOTE Hysterectomy. We collected data on a private shared drive noting patient demographics, indications for surgery, operation outcomes and patient follow-up details. Results and Conclusions: : Between January and December 2018, 33 patients underwent surgery between two units. Indications for surgery included dysfunctional uterine bleeding, endometrial hyperplasia, pelvic pain, post-menopausal bleeding, prophylactic surgery in BRCA positive patients and one grade 1 stage 1 endometrial cancer in whom laparoscopic hysterectomy was technically difficult and complicated by previous midline laparotomy. Ages ranged from 35 to 75 and BMI from 20-53. Mean operation time was 68.5 min and mean blood loss intraoperatively was 269mls. 15.2% (n = 5) had a blood loss equal or more than 500 mls. There were no intraoperative complications and no conversions to open surgery. The median visual analogue pain score at 6 h post operatively and at discharge was 0. All patients received regular Paracetamol and Ibuprofen and opiate based analgesics were only used on an as required basis. Postoperative complication which included failed trial without catheter, urinary tract infection and urinary dysfunction were reported by four women (12.4%). Only 2 patients re-presented to hospital over a 30-day period and neither required inpatient management. Hysterectomy by vNOTES has advantages over traditional laparoscopic and vaginal hysterectomy that include reduced requirement for intra-abdominal insufflation and head down, absence of trocar related injuries and easier operative access in patients with morbid obesity, or previous abdominal surgery such as midline laparotomy or mesh hernia repair. In addition, both tubes and ovaries can be removed easily due to easier access and visibility and there is no requirement for vaginal descent in order to do so. Plans for a comparative study between laparoscopic hysterectomy and vNOTES hysterectomy are underway.